2018
DOI: 10.3144/expresspolymlett.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Combined compatibilization and plasticization effect of low molecular weight poly(lactic acid) in poly(lactic acid)/poly(3-hydroxybutyrate-co-3-hydroxyvalerate) blends

Abstract: Abstract. Improving overall properties of poly(lactic acid) (PLA) by blending it with another biobased polymer has been a strong field of research over the last years. In this study we demonstrate the synergetic effect of a small amount (between 0.1 and 1 wt%) of oligomer-like PLA (oLA) on the thermal, mechanical and gas barrier properties of the widely studied PLA-poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) blends (90-10 wt%). Films of PLA/PHBV/oLA blends were prepared via single-screw extrusion. oLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
5
12
0
Order By: Relevance
“…Particularly, the blend containing 10 wt% of OLA showed the highest barrier properties with a WVP value of 0.65 × 10 −14 kg·m/m 2 ·Pa 1 ·s 1 . This barrier enhancement can be attributed to the densification of PLA produced by the increase in crystallinity after the OLA addition [47], which was also previously corroborated by DSC and DMTA. Similar results were reported by Ambrosio-Martín et al [44], who associated the reduction of the vapor permeability with an effect of "antiplasticization".…”
Section: Barrier Properties Of the Pla/ola/hnts Filmssupporting
confidence: 77%
“…Particularly, the blend containing 10 wt% of OLA showed the highest barrier properties with a WVP value of 0.65 × 10 −14 kg·m/m 2 ·Pa 1 ·s 1 . This barrier enhancement can be attributed to the densification of PLA produced by the increase in crystallinity after the OLA addition [47], which was also previously corroborated by DSC and DMTA. Similar results were reported by Ambrosio-Martín et al [44], who associated the reduction of the vapor permeability with an effect of "antiplasticization".…”
Section: Barrier Properties Of the Pla/ola/hnts Filmssupporting
confidence: 77%
“…D. Lascano et al [51] reported a decrease of PLA T g from 63.3 • C (neat PLA; different grade) down to 50.8 • C with 20% OLA (different commercial grade of OLA). Armentano et al [58] reported a dual plasticization effect of PHB and OLA on PLA, but the decrease in T g was not as important as the above-mentioned by Burgos et al Moreover, Amor et al [59], reported a slight plasticization effect on PLA/PHBH blends by using OLA in pellet form with a dual plasticization effect of PHBH (which provided a 3 • C decrease in T g of PLA with a PHBH loading of 10 wt %) and OLA (which provided a decrease of 1 • C with a load of 1 wt %). All these results show the disparity in plasticization of PLA with OLA even they share the same chemical structure.…”
Section: Thermal Properties Of Phbh-asf/ola Compositesmentioning
confidence: 88%
“…Miscibility and compatibility of polyester blends containing PLA and PHAs, such as PHB or poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) depend on the molar mass and crystallinity of the components, on the blending method and the composition of the blend. e blends are immiscible when the molar mass of components is high [27]. A decrease of molar mass of one of the blend components results in a reduction of the phase separation [28].…”
Section: Effects Of Miscibilitymentioning
confidence: 99%